Increased pressure-induced tone in rat parenchymal arterioles vs. middle cerebral arteries: role of ion channels and calcium sensitivity - Cipolla, Marilyn J. (American Physiological Society, 2014)
Brain parenchymal arterioles (PAs) are high-resistance vessels that branch off pial arteries and perfuse the brain parenchyma. PAs are the target of cerebral small vessel disease and have been shown to have greater pressure-induced tone at lower pressures than pial arteries. We investigated mechanisms by which brain PAs have increased myogenic tone compared with middle cerebral arteries (MCAs), focusing on differences in vascular smooth muscle (VSM) calcium and ion channel function. The amount of myogenic tone and VSM calcium was measured using Fura 2 in isolated and pressurized PAs and MCAs. Increases in intraluminal pressure caused larger increases in tone and cytosolic calcium in PAs compared with MCAs. At 50 mmHg, myogenic tone was 37 ± 5% for PAs vs. 6.5 ± 4% for MCAs (P < 0.01), and VSM calcium was 200 ± 20 nmol/l in PAs vs. 104 ± 15 nmol/l in MCAs (P < 0.01). In vessels permeabilized with Staphylococcus aureus α-toxin, PAs were not more sensitive to calcium, suggesting calcium sensitization was not at the level of the contractile apparatus. PAs were 30-fold more sensitive to the voltage-dependent calcium channel (VDCC) inhibitor nifedipine than MCAs (EC(50) for PAs was 3.5 ± 0.4 vs. 82.1 ± 2.1 nmol/l for MCAs;P < 0.01); however, electrophysiological properties of the VDCC were not different in VSM. PAs had little to no response to the calcium-activated potassium channel inhibitor iberiotoxin, whereas MCAs constricted ∼15%. Thus increased myogenic tone in PAs appears related to differences in ion channel activity that promotes VSM membrane depolarization but not to a direct sensitization of the contractile apparatus to calcium.